‘Trying to make it matter’: The challenges of assimilating a resettlement culture into a ‘local’ prison - Cracknell, Matthew (Criminology & criminal justice, 2023)
As part of the Transforming Rehabilitation reforms, 70 ‘local’ prisons in England and Wales were re-designated as resettlement prisons, in order to provide additional through-the-gate support to individuals serving short sentences. Drawing on staff and prisoner interviews in one case study resettlement prison, this article considers what challenges were involved with implementing a resettlement culture in a local prison. Findings first outline factors inhibiting the resettlement status of the prison; these include a tension between attempts to implement a more expansive resettlement remit into the prison, while also fulfilling more long-standing core institutional duties; the size and churn of the prison population; wide-scale apathy caused by change fatigue; and government austerity policies which caused significant difficulties in the day-to-day staffing of the prison. This article then turns to practitioner responses to the re-designation, finding that practitioners interpreted resettlement in two limited ways: top-down managerial attempts to instil a wider resettlement culture into the prison, and resistance from prison officers who felt unwilling or unable to expand their roles beyond custodial and security concerns. This article concludes by outlining how this set of inter-related barriers frustrated staff and prisoners alike, eroding a sense of hope and purpose and impeding true cultural change.